8OTargeting EGFR exon 20 insertions in non-small cell lung cancer by exploiting a dependency on parallel SRC signalling. (7th November 2019) - Vyse, S; Chen, N; Oddy, J; Harrison, P; Le, A; Estrada-Bernal, A; Hermsen, M; Doebele, R; Huang, P
Abstract: Background: Inframe insertions in exon 20 of the epidermal growth factor receptor (EGFR) gene are oncogenic drivers in non-small cell lung cancer (NSCLC). However, unlike more common EGFR mutations, low frequency EGFR exon 20 insertions are resistant to clinically approved EGFR inhibitors and are associated with poor patient prognosis. There is an unmet clinical need to identify novel therapies that will be effective for patients with EGFR exon 20 insertions. Methods: Cell viability of three patient-derived NSCLC cell line models harbouring EGFR exon 20 insertions, CUTO14 (A767_V769dupASV), CUTO17 (N771_H773dupNPH) and CUTO18 (S768_D770dupSVD) was assessed after treatment with a chemical compound screen targeting cancer-associated pathways. Western blotting was used to probe cell signalling following dasatinib treatment. Mutant SRC expression constructs were introduced into cell lines via lentiviral transduction and depletion of endogenous SRC levels was achieved using RNAi. Models of acquired drug resistance were developed by long-term drug exposure. Results: Out of 58 screened compounds, the tyrosine kinase inhibitor dasatinib was a shared hit across all EGFR exon 20 insertion models and was superior to the EGFR inhibitor gefitinib in cell viability and apoptosis assays. Dasatinib sensitivity was rescued by expression of a gatekeeper mutant SRC that does not bind dasatinib, whilst all models were sensitive to RNAi-mediated depletion of endogenous SRC expression. Importantly, models of acquired dasatinib resistance maintain sensitivity to poziotinib, an EGFR inhibitor that can target EGFR exon 20 insertions. Similarly, dasatinib effectively inhibits cell viability of a model of acquired resistance to poziotinib, indicating two independent, targetable signalling nodes. Combined treatment with dasatinib and poziotinib prevented the emergence of drug resistance. Conclusions: EGFR exon 20 insertion lung cancer models are sensitive to inhibition of parallel SRC signalling via dasatinib treatment. In a patient population with limited therapeutic options, an upfront rational combination of dasatinib with EGFR inhibitors that target EGFR exon 20 insertions has the potential to achieve durable responses. Legal entity responsible for the study: Paul Huang. Funding: Institute of Cancer Research, Cancer Research UK. Disclosure: R. Doebele: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses, Licensing / Royalties: Genentech/Roche; Advisory / Consultancy, Travel / Accommodation / Expenses, Licensing / Royalties: Ignyta; Licensing / Royalties: Foundation Medicine; Advisory / Consultancy, Licensing / Royalties: Loxo Oncology; Advisory / Consultancy: Bayer; Advisory / Consultancy, Shareholder / Stockholder / Stock options, Licensing / Royalties: Rain Therapeutics; Honoraria (self), Advisory / Consultancy: Takeda/Millenium; Licensing / Royalties: Abbot Molecular. All other authors have declared no conflicts of interest.